INSIDE-OUTSIDE CIRCLE AS THE WAY IN BUILDING STUDENTS’ MOTIVATION AND INTERACTION IN SPEAKING CLASSROOM ACTIVITIES - Tiwery, Sartin Dian (International Journal of Language Education, 2019)
ABSTRACT As the important factors in EFL speaking classroom activities, building students’ motivation and interaction in EFL speaking classroom should be designed in meaningful ways. Many research studies reported the variety ways in minimizing the problems as well as proposed innovative ways in teaching speaking skill. One of the ways that recommended by the researches is inside-outside circle strategy. It is a way that students can work cooperatively and raise their motivation to talk and interact with others. The classroom-based research was conducted with only one cycle implemented the strategy. 30 students at the first grade of Multimedia Program at SMK Negeri 6 Ambon were participated in this study. The results showed that during the implementation of inside-outside circle strategy in the classroom activities, the students could actively involve in expressing their ideas based on the given topics, they could build good interaction in the inside and outside a group, and showed high motivation in speaking classroom activities.